Hubungan Berat Badan Bayi Baru Lahir dengan Kejadian Ruptur Perineum Persalinan Normal - Cici Angraini; Kartika Sari; Nurdiana; desi_safitri08 desi_08; Bq Yulia Sri Aprian (Universitas Ngudi Waluyo, 2022)
Perineal rupture is the second leading cause of vaginal delivery. Factors causing perineal rupture include delivery position, how to push, delivery leadership, newborn weight and condition of the perineum. The greater the birth weight of the baby, the greater the risk perineal rupture. From 8 multiparous mothers in March 2011 It was found that most of the mothers had grade I lacerations as many as 4 people with normal birth weight (2500-4000 g). The majority of mothers who gave birth experienced grade I lacerations with adequate birth weight (between 2500-4000 grams) as many as 40 people (48.8%), while at least the mothers who gave birth experienced grade IV lacerations with a baby's birth weight more (more than 4000 grams). ) as many as 1 person (1,2%). For this reason, health workers are expected to carry out early detection and monitoring of fetal growth and development and provide IEC to pregnant women regarding the relationship between newborn weight and birth canal lacerations. Abstrak Ruptur perineum penyebab kedua pada persalinan pervaginam. Faktor penyebab ruptur perineum antara lain posisi persalinan, cara meneran, pimpinan persalinan, berat badan bayi baru lahir dan keadaan perineum. Semakin besar berat badan bayi yang dilahirkan akan meningkatkan resiko terjadinya ruptur perineum. Dari 8 orang ibu multipara pada bulan Maret 2011 didapatkan sebagian besar ibu mengalami Laserasi derajat I sebanyak 4 orang dengan berat badan lahir normal (2500-4000 gr). Mayoritas ibu bersalin mengalami laserasi derajat I dengan berat badan lahir bayi cukup (antara 2500-4000 gram) sebanyak 40 orang (48,8 %), sedangkan paling sedikit ibu bersalin mengalami laserasi derajat IV dengan berat badan lahir bayi lebih (lebih dari 4000 gram) sebanyak 1 orang (1,2 %). Untuk itu petugas kesehatan diharapkan melakukan deteksi dini dan pemantauan tumbuh kembang janin serta memberikan KIE kepada ibu hamil mengenai kaitan berat badan bayi baru lahir.